FOOD PRODUCT PACKAGING DESIGN AS MARKETING TOOLS IN PURCHASE DECISION - Ajeng Septiana Wulansari (Management and Leadership Study Programme, 2019)
This study examines the impact of packaging design on food packaging elements consisting of two independent variables (visual elements and information elements) on purchasing decisions, and also customer involvement and time pressure as moderating variables. Data collected using questionnaires and focus group discussions were used to find the right questions for the moderating variable. The hypothesis was tested using logistic regression because the purchase decision as the dependent variable only had two alternative answers (binary): yes (buy) or no (not to buy). Results show that three of the four elements have a significant effect on purchasing decisions, there are graphics and color, size and shape of packaging, and product information. Visual elements, graphics and product size and shape have a positive impact on purchasing decisions on low customer engagement and information elements affecting purchasing decisions at a higher level of engagement such as for customers who adopt healthy living.